Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time